The Influence Of The Sociodrama Method On Increasing Students' Learning Motivation In Learning The History Of Events Surrounding The Proclamation in Class XIA of SMA Negeri 1 Bunyu - Sinaga, Haposan; Kumalasari, Dyah; Zulkarnain, Zulkarnain (STKIP Singkawang, 2024)
This research was conducted with the aim of finding out how to increase student motivation in learning history by using a sociodrama model on the main material of events surrounding the proclamation in Class XI A of SMA Negeri 1 Bunyu for the 2023/2024 academic year. The research method used in this research is the experimental method, which explains students' learning motivation in the History subject with the subject matter of Events Surrounding the Proclamation in Class XI A at SMA Negeri 1 Bunyu for the 2023/2024 academic year. The design used in this research is One Group Pretest – Posttest Design. The subjects of this research were 25 students in Class XI A, Academic Year 2023/2024, consisting of 17 female students and 8 male students. Data collection techniques were carried out using tests before treatment (pretest) and after treatment (posttest). The sampling approach used in this research is a saturated sample. The results of this research prove that there is a significant difference in student motivation before and after applying the sociodrama method for class XI A students at SMA Negeri 1 Bunyu for the 2023/2024 academic year. The results of the paired t-test show a significant value of 0.000 < 0.05, which means the influence given is significant. The pretest data obtained a mean of 59.48 and the posttest data obtained a mean of 79.24, where there was an increase in the average of 19.76 points.